A simple method for pedicle protection in flap surgery for posterior heel defects - Kamath J (Indian Journal of Plastic Surgery)
A simple method is being described to avoid pressure over the pedicle of the flaps that are being used to cover the posterior aspect of the heel, using two 5/8 Ilizarov rings. This adjuvant procedure in the difficult area of reconstructive surgery ensures safer early postoperative care and better patient comfort.